2014
DOI: 10.2217/pgs.14.92
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole and Atazanavir: A CYP2C19-Dependent Manageable Drug–Drug Interaction

Abstract: Voriconazole exposure was variable but Ctrough levels were above 1000 ng/ml in all patients; one CYP2C19 intermediate metabolizer required lower doses of voriconazole (50 mg twice daily) to obtain satisfactory drug concentrations. Atazanavir and ritonavir plasma levels were moderately reduced (area under the curve: -23 and -26%, respectively); raltegravir exposure seemed increased by voriconazole administration (area under the curve: 2.5-fold higher) in a single subject. Coadministration of atazanavir and vori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Nine studies report an association between intermediate metabolizers and voriconazole metabolism and concentrations [14, 18, 19, 34, 39, 43], though several did not conduct statistical analyses [35, 44, 45]. However, almost every study found that IMs had decreased voriconazole metabolism and increased concentrations as compared to NMs.…”
Section: Cyp2c19mentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies report an association between intermediate metabolizers and voriconazole metabolism and concentrations [14, 18, 19, 34, 39, 43], though several did not conduct statistical analyses [35, 44, 45]. However, almost every study found that IMs had decreased voriconazole metabolism and increased concentrations as compared to NMs.…”
Section: Cyp2c19mentioning
confidence: 99%
“…As with PMs, very little evidence exists for an effect of IM genotypes on clinical outcome. One case report noted an individual with the *1/*2 genotype who required a dose reduction due to high trough concentrations [45], and another case report noted an individual with the *1/*2 genotype who had elevated concentrations accompanied by hallucinations and abnormal liver function tests. The latter patient’s adverse effects resolved after stopping voriconazole treatment, and reintroduction at a lower dose was uncomplicated [46].…”
Section: Cyp2c19mentioning
confidence: 99%
“…Many commonly prescribed drugs are metabolized, inhibited, or induced by the main ATV metabolizing enzymes CYP3A4/5 so there is a high potential for drug-drug interactions, especially in older patients where polypharmacy is common, and in patients co-infected with hepatitis C, tuberculosis, or other opportunistic bacterial or fungal infections, a common complication in individuals with HIV [48]. A case series in four HIV positive patients reported that ATV and ritonavir C min and AUC were only moderately reduced in patients administered voriconazole, a triazole antifungal agent [49]. A recent study in healthy volunteers reported that co-administration of ATV/r with voriconazole also lead to reductions of ATV C min of between 20–30% regardless of the metabolizer phenotype of the primary metabolizing enzyme of voriconazole, CYP2C19 .…”
Section: Drug-drug Interactionsmentioning
confidence: 99%